Comparison of pupil diameter and tear production in dogs treated with acepromazine, tramadol and their combination - Paulo Henrique de Albuquerque Santos; Kelly Cristine de Sousa Pontes; Rogério Pinto; Paula Baêta da Silva Rios; Gláucia Matos Marques da Silva; Andréa Pacheco Batista Borges; Lukiya Silva Campos Favarato (Revista Ceres, 2013)
Some ophthalmic surgeries require induction of mydriasis, however, drugs traditionally used for this purpose significantly reduces tear production. To evaluate the effect of acepromazine and tramadol, used alone or in combination, on pupil diameter, tear production, heart and respiratory rate, systolic blood pressure and rectal temperature, these drugs were administered to seven clinically normal dogs divided into three experimental groups (G1 - acepromazine; G2 - tramadol; G3 - tramadol + acepromazine) that differed only in the sedation protocol. Parameters were measured in four experimental moments. Miosis occurred in G1, in addition to reduced tear production and respiratory rate. No significant changes were found in the parameters assessed in G2, whereas in G3, there was decrease in tear production of the right eye, decrease in the respiratory rate and rectal temperature. Tramadol proved to be a drug suitable for pre-anesthetic procedures that require the maintenance of pupil diameter and keeps the tear production within normal parameters. However, the use of acepromazine alone or in combination with tramadol requires protection of the patient's eye surface to prevent the occurrence of undesirable ophthalmic changes.